AsiaPacifiQueer : rethinking genders and sexualities - Martin, Fran, 1971-; McLelland, Mark J., 1966-2020; Yu, Audrey (University of Illinois Press, 2008)
"A multidisciplinary, multicultural reassessment of gender and sexuality in the Asian Pacific"--Publisher's description
Keywords: Homosexuality -- Asia.; Gay people -- Asia.; Gay people in popular culture -- Asia.; Homosexualité -- Asie.; Personnes homosexuelles -- Asie.; Personnes homosexuelles dans la culture populaire -- Asie.; SOCIAL SCIENCE -- Gay Studies.; SOCIAL SCIENCE -- Ethnic Studies -- General.; Gay people; Homosexuality; Asia; Homosexualität; Asiatisch-Pazifischer Raum; Sexualitet -- identitet -- genus -- Asien.; Populärkultur.; Homosexualitet -- lesbianism.; Homosexualitet -- Asien.; Homosexuella -- Asien.; Populärkultur -- homosexuella.; Asian LGBTQ+ people; LGBTQ+ culture; Gender identity; Aufsatzsammlung.